2008
DOI: 10.1021/ma800145s
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Thermoresponsive Behaviors of a Well-Defined Pyrrolidone Based Hydrophilic Polymer

Abstract: A well-defined pyrrolidone based thermoresponsive polymer, poly [N-(2-methacryloyloxyethyl) pyrrolidone] (PNMP), was synthesized via reversible addition-fragmentation chain transfer radical polymerization or RAFT polymerization of N-(2-methacryloyloxyethyl) pyrrolidone monomer in methanol under a mild Visible light radiation at 30 °C. The average molecular weights and polydispersity indices of PNMP polymers were characterized by gel permeation chromatography (GPC) and static light scattering analysis. The ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 64 publications
(91 reference statements)
4
82
3
Order By: Relevance
“…Increasing [PAAEMA] 0 :[CPFDB] 0 :[TPO] 0 from 50:1:0.3 to 100:1:0.3, and finally to 150:1:0.3 leads to the decrease of slope, indicating that higher [PAAEMA] 0 :[CPFDB] 0 :[TPO] 0 leads to slower polymerization rate. This tendency is contrary to what observed in RAFT polymerization of GMA monomer47 or pyrrolidone‐derived methacrylic monomer55 under the same polymerizing conditions. Clearly, more experiments are necessary to clarify this phenomenon, but beyond the scope of this article.…”
Section: Resultscontrasting
confidence: 97%
“…Increasing [PAAEMA] 0 :[CPFDB] 0 :[TPO] 0 from 50:1:0.3 to 100:1:0.3, and finally to 150:1:0.3 leads to the decrease of slope, indicating that higher [PAAEMA] 0 :[CPFDB] 0 :[TPO] 0 leads to slower polymerization rate. This tendency is contrary to what observed in RAFT polymerization of GMA monomer47 or pyrrolidone‐derived methacrylic monomer55 under the same polymerizing conditions. Clearly, more experiments are necessary to clarify this phenomenon, but beyond the scope of this article.…”
Section: Resultscontrasting
confidence: 97%
“…In contrast, as shown in the bottom figure of Figure 3b, this hysteresis could not be detected on heating and then cooling the solution of PNMEP 57 ‐ b ‐P(NMEP 7 ‐ stat ‐FPHPMA 6 ) or PNMEP 63 ‐ b ‐PFPHPMA 7 . As previously observed by Lutz et al,13 Li and coworkers,14 Wu and coworkers15 and our group,16 the hysteresis was negligible on heating‐cooling the aqueous solutions of random copolymers based on oligo(ethylene glycol) methacrylate and 2‐(2‐methoxyethoxy)ethyl methacrylate, oligo(ethylene glycol) acrylate and 2‐(5,5‐dimethyl‐1,3‐dioxan‐2‐yloxy)ethyl acrylate, and the homopolymers of pyrrolidone‐based (meth)acrylates, whose phase transitions were mainly induced by the hydrophobic association of apolar or less polar polymer backbones and unit spacers. Accordingly, it may be concluded that the H‐bonding that had been already consumed during preorganization (see Figure 2) did not contribute to this thermo‐triggered phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…The size distribution of the resulting hGPs was characterized by dynamic light scattering (DLS) and the result is shown in Fig. [27][28][29][30][31][32] As step-two reaction took Intuitively, one would expect the particles to grow in size as the reaction time prolongs.…”
Section: Reaction Timementioning
confidence: 99%